The impact of protection status, local people’s awareness and hunting pressure on conservation of delacour’s langur (\(Trachypithecus delacouri\)) in northern Vietnam - Vinh Thanh, Nguyen; Tuan Anh, Nguyen; Minh Ha, Do; Thi Hue, Dao; Bich Thuy, Pham; Thanh Hai, Dong; Van Duan, Dinh (Academia Journal of Biology, 2022)
During 2019 and 2020, 14 areas in Northern Vietnam were surveyed for Delacour’s langur Trachypithecus delacouri (Osgood, 1932) to confirm the status of distribution, estimated populations and intensity of hunting pressure. People from elected local authorities, as well as other individuals, were interviewed to determine their awareness of the langur’s conservation. These data were combined for statistical analysis. The results showed that protection status was negatively correlated with hunting pressure (Rs = -0.601; p = 0.006). Hunting pressure also had a negative relationship with the growth of the number of langur populations (Rs = -0.616; p = 0.005) and the number of langur individuals (Rs = - 0.578; p = 0.01). However, placing an area under State protection had no correlation with the growth of the population of Delacour's langur living there (p > 0.05). People's awareness in Van Long Nature Reserve was very high (over 99% strongly supported the conservation of Delacour’s langur) which corresponded to the growth of Delacour's langur population in that area. To protect both the langurs and people's livelihoods, we, therefore, recommend turning the areas where Delacour's langurs are distributed into protected areas and also promoting people’s awareness through legal dissemination and activities. The reintroduction of the species into suitable protected habitats should be carried out scientifically.